Faktor-Faktor yang Mempengaruhi Financial Distress: Pendekatan Model Springate dan Grover (Studi Empiris pada Badan Usaha Milik Negara Periode 2015-2019) - Ferdinar Bayu Setiaji Pratama; Rita Wijayanti (Neolectura, 2021)
Financial distress is a condition in the stage of financial decline that occurs before the occurrence of bankruptcy or liquidation. This study aims to examine the factors that affect financial distress in State-Owned Enterprises (BUMN). The independent variables tested were managerial compensation, working capital, investment growth, operating cash flow, and leverage. Financial distress in this study was measured by the springate method and the grover method. This study selects the sample by purposive sampling method. With the final result as many as 58 samples for 6 years of observation. Research data for the period 2014-2019 was analyzed using multiple linear regression analysis. The results showed that the working capital and leverage variables had an influence on financial distress. Managerial compensation, investment growth, and operating cash flow have no effect on financial distress.